The HECT family of E3 ubiquitin ligases and PTEN. (October 2022) - Song, Min Sup; Pandolfi, Pier Paolo
Abstract: Members of the HECT family of E3 ubiquitin ligases have emerged as prominent regulators of PTEN function, subcellular localization and levels. In turn this unfolding regulatory network is allowing for the identification of genes directly involved in both tumorigenesis at large and cancer susceptibility syndromes. While the complexity of this regulatory network is still being unraveled, these new findings are paving the way for novel therapeutic modalities for cancer prevention and therapy as well as for other diseases. Here we will review the signal transduction and therapeutic implications of the cross-talk between HECT family members and PTEN.